Adherence of Surgeons to Antimicrobial Prophylaxis Guidelines in a Tertiary General Hospital in a Rapidly Developing Country - Ahmed Abdel-Aziz; Ayman El-Menyar; Hassan Al-Thani; Ahmad Zarour; Ashok Parchani; Mohammad Asim; Rasha El-Enany; Haleema Al-Tamimi; Rifat Latifi (Advances in Pharmacological Sciences)
Objectives. To assess the standard practice of care of surgeons regarding surgical antibiotic prophylaxis, to identify gaps, and to set recommendations. Methods. A retrospective analysis of data obtained from different surgical units in a single center in Qatar over a 3-month period in 2012. A total of 101 patients who underwent surgery and followed regimes for surgical prophylaxis as per hospital guidelines were included in the study. Results. The overall use of antibiotic was 89%, whereas the current practice did not match the recommended hospital protocols in 53.5% of cases. Prolonged antibiotics use (59.3%) was the commonest reason for nonadherence followed by the use of an alternative antibiotic to that recommended in the protocol (31.5%) and no prophylaxis was used in 9.2% of cases. The rate of compliance was significantly higher among clean surgery than clean contaminated group (P=0.03). Forty-four percent of clean and 65% of clean-contaminated procedures showed noncompliance with the recommended surgical antimicrobial prophylaxis hospital guidelines. Conclusion. Lack of adherence to hospital protocols is not uncommon. This finding remains a challenge to encourage clinicians to follow hospital guidelines appropriately and to consistently apply the surgical antibiotic prophylaxis. The role of clinical pharmacist may facilitate this process across all surgical disciplines.